Detection of antibodies to Toxoplasma gondii in neotropical primates from São Paulo state, Brazil - DE MOURA, H; ADANIA, CH; SOARES, HS; SILVA, JCR; GENNARI, SM; CARDOSO, L; LOPES, AP (Journal of the Hellenic Veterinary Medical Society, 2022)
Toxoplasmosis is a life-threatening disease in neotropical primates. The aim of the present study was to determine the frequency of antibodies to Toxoplasma gondii in neotropical primates from São Paulo state (SP), Brazil. The modified agglutination test (MAT, cut-off: 25) was used in 49 neotropical primates upon or after their admission to Associação Mata Ciliar (Jundiaí, SP, Brazil). Eight of the 49 animals (16.3%) were seropositive. The genus Sapajus had the highest antibody titer (12,800), followed by the genus Callithrix (3,200). No association (p> 0.05) was found between seroprevalence and genera (Alouatta, Callicebus, Callithrix, and Sapajus), sex or age. The three positive primates of the genera Allouataand the one of the genera Callithrix died, whereas the two seropositive Sapajus were alive. Further studies on the epidemiology of T. gondii infection are necessary in a larger sample size of captive and wild neotropical primates.